Importance of design in educational process of foresters - DUDARCHUK, Galina (Journal of Education, Technology and Computer Science, 2013)
The basic positions of project-based learning in training future foresters are presented, determined students’ commitment to this method and highlights students suggestions improve the teaching of special subjects